Language Disruption in the Era of Artificial Intelligence and Its Implications for the Indonesian Language Curriculum - Aisah Natalia Syafitri; Vebby Andra; Heny Friantary (JMiE (Journal of Management in Education), 2026)
This study aims to analyze the phenomenon of language disruption in the era of Artificial Intelligence (AI) and its implications for Indonesian language learning and curriculum development. The study used a qualitative, descriptive approach. Data were collected through literature studies, observations of the use of AI in learning, and analysis of curriculum documents. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and conclusion drawing. The results show that language disruption in the AI era is characterized by three main forms: automation of language production, language standardization, and simplification of language structure. These three phenomena impact students' language competencies, such as a decline in manual writing skills, an increase in evaluative skills regarding texts, and a growing dependence on technology. On the other hand, AI also has the potential to improve digital literacy and critical thinking skills if utilized appropriately. Implications for the Indonesian language curriculum include the need for integration of AI literacy, strengthening critical literacy, and digital ethics education. The curriculum must transform from one oriented towards structural aspects to a more contextual, adaptive, and technology-based approach.